2018
DOI: 10.5797/jnet.oa.2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Application of C-arm CBV Measurement for Evaluation before and Immediately after Neuroendovascular Treatment

Abstract: Objective: To evaluate changes related to cerebral endovascular treatment, a C-arm cerebral blood volume (CBV) study was performed before and after treatment. Although conditions related to treatment-administered contrast medium of the pretreatment examination differs from that for post-treatment, no study has investigated the effect on the results. In this study, we examined differences in the results of the C-arm CBV examination before and after treatment in patients who underwent carotid artery stenting (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…3) However, in qualitative evaluation to mainly identify the area with abnormal brain tissue has been mainly reported. [4][5][6][7][8][9] In addition, improvement of the angiography system and data acquisition methods has recently been tried and experimental studies on C-arm CTP described in this study have been occasionally reported. 1-3,10,13-19) Figure 6 outlines the three approaches for cerebral perfusion imaging using contrast medium performed at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) However, in qualitative evaluation to mainly identify the area with abnormal brain tissue has been mainly reported. [4][5][6][7][8][9] In addition, improvement of the angiography system and data acquisition methods has recently been tried and experimental studies on C-arm CTP described in this study have been occasionally reported. 1-3,10,13-19) Figure 6 outlines the three approaches for cerebral perfusion imaging using contrast medium performed at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…C-arm CBV is acquired at steady state of contrast medium flow in brain tissue. [4][5][6][7][8][9] Since acquired information is limited to CBV, this method is useful to detect cerebral infarction, as a region with reduced CBV reflecting cerebrovascular occlusion-induced blockage of blood flow. However, the information in a CBV image is insufficient to evaluate mismatch between the area perfused by the occluded vessel and the salvageable ischemic area.…”
Section: Introductionmentioning
confidence: 99%